2007
DOI: 10.1080/15252019.2007.10722127
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward Location-based Advertising

Abstract: Location-based advertising (LBA) is not new but being able to access it through one's mobile communication device is. Description of this revolutionary advertising medium is provided as well as some opportunities and challenges that come with it. Desperately needed is more scholarly research since in-depth examination of the topic has barely begun. To assist researchers in their investigations, a scale is provided here that is likely to become central to many studies: attitude toward location-based advertising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 35 publications
1
80
0
9
Order By: Relevance
“…Sundar (2008b) argues that some modalities that are unique to digital media (e.g., pop-up ads on websites) tend to negatively influence content evaluations because they appear unsolicited, causing disturbance and irritation. Given that the mere recognition of an advertising attempt is intrusive enough to cause psychological disturbance (Edwards et al, 2002) and that unwanted information distracts users even when it is in fact useful (Bruner & Kumar, 2007), the sudden, unexpected appearance of LBA on mobile devices may lead to involuntary recognition of the ad, thus hijacking user attention and interfering with cognitive processing (Edwards et al, 2002). Thus, perceived intrusiveness in advertising generally has negative effects on user attitudes toward ad content.…”
Section: Perceived Intrusivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Sundar (2008b) argues that some modalities that are unique to digital media (e.g., pop-up ads on websites) tend to negatively influence content evaluations because they appear unsolicited, causing disturbance and irritation. Given that the mere recognition of an advertising attempt is intrusive enough to cause psychological disturbance (Edwards et al, 2002) and that unwanted information distracts users even when it is in fact useful (Bruner & Kumar, 2007), the sudden, unexpected appearance of LBA on mobile devices may lead to involuntary recognition of the ad, thus hijacking user attention and interfering with cognitive processing (Edwards et al, 2002). Thus, perceived intrusiveness in advertising generally has negative effects on user attitudes toward ad content.…”
Section: Perceived Intrusivenessmentioning
confidence: 99%
“…LBA uses location-tracking technologies such as the Global Positioning System (GPS) and Galileo Global Navigation Satellite System (GNSS) to pinpoint users' real-time locations and deliver location-specific ads on their mobile devices. Ads delivered via mobile LBA tend to be highly individualized, with instant, personalized, and location-aware characteristics that cater to the specific needs of each ad recipient (Bruner & Kumar, 2007;Dhar & Varshney, 2011). Such individualization and geo-conquesting serve to make LBAs more likely to attract click-throughs because of the timeliness of the ad offers.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the push-oriented LBAM has two options. One is opt-in, which sends advertising messages only after obtaining the users' permission; the other is opt-out, which directly sends messages without permission until the users refuse the receipt of the messages (Bruner & Kumar, 2007;Unni & Harmon, 2007). Based on one of their experimental findings, Unni and Harmon (2007) reported that consumers prefer the pull-oriented LBAM because of their concern on intrusiveness.…”
Section: Location-aware Mobile Advertisingmentioning
confidence: 99%
“…For any pair of the S states on floor k, the probability that their next S states are on floor m (k < m) is 1/(f − k) 2 . We know the probability of merging any two S states on floor m is p m .…”
Section: B Finding Pmentioning
confidence: 99%
“…Such applications can be microblogging [1], location based advertising [2], local traffic [3], etc. In a multi-floor building environment, knowing the floor level of a mobile user is particularly useful to a variety of LBAs.…”
Section: Introductionmentioning
confidence: 99%